A sandwich-type three-dimensional layered double hydroxide nanosheet array as a novel fiber coating for headspace solid-phase microextraction of phenols from water samples - Marzieh Piryaei; Mehdi Abolghasemi (Nanochemistry Research)
In the present study, graphene oxide nickel-titanium layered double hydroxide (NiTi-LDH/GO) was synthesized. NiTi-LDH/GO was used as a fiber coating for the determination of phenolic compounds for headspace solid‐phase microextraction methods in water samples. These extracted components were introduced into a gas chromatography-mass spectrometry (GC-MS) injection port for further analysis. The following analytical merits were used under optimal conditions: temperature of extraction: 80 ºC, desorption duration: 2 min, extraction time: 40 min, temperature time:  270 oC, salt concentration: 10% (w/v), 0.01–100 µg L-1 and 0.004-0.09 ng mL-1 for dynamic linear rang (DLR) and limit of detection (LOD), respectively. The repeatability under optimal conditions for one fiber (n = 3) is given as the relative standard deviation (R.S.D. %) which was between 6.5 % and 9.9% for these compounds. The results of the experiments clearly indicate that the NiTi- LDH /GO nanostructure fiber is an appropriate choice for HS-SPME of phenols analysis. By combining HS-SPME using NiTi- LDH /GO nanostructure fiber and GC-MS, low LODs can be achieved which can be used for determining phenols from water samples.